Saberes sociais e memórias de territórios camponeses em Goiás (pós 1964) - Borges, Joyce de Almeida (2019)
The study in question derived from the research line “Education, work and social movements” of the Postgraduate Program in Education and seeks to understand how the leaderships present in peasant social movements, in Basic Ecclesial Communities, and in rural workers’ unions play determining roles in the confrontation between the agrarian capital and the peasantry. The scientifics problemas: has the social knowledge been fundamental to the consolidation of the struggles in the field in Goiás? How and to what extent? What do the subjects’ memories have to say about this historical moment? In this preamble, the general objective of this thesis has been to value the knowledge and the recent memories of peasant leaderships related to the conflicts in the field in Goiás. We have analyzed the actions developed and the intermediations, the memories of struggles and the actors’ resistances related to the Movement of Landless and Free Land Rural Workers. The memories have brought information that made it possible to make connections between different historical moments of the struggle for land in Goiás, as well as the violence suffered by peasants. The methodology used for the reflection comes from readings related to the theme, the observations in camps, analysis of interviews and collection of testimonies as part of the historical process of rights denied during the territorial disputes experienced in Goiás. Considering the historical and dialectical materialism, this research has strengthened the debate in the field of the research in education and current agrarian geography. As a result of this reflection, some notes have been made that social knowledge can be constructed from social confrontations, through dialogue, collective and individual actions, and pedagogical constructions of everyday life, by means of training, such as participation in the meetings, in the mystiques, in circles of debates, in courses, in work teams, occupations and lectures. This knowledge, in turn, enables new practices of collective and popular confrontation in the formation of new historical subjects capable of performing a more critical and political reading of the world. Knowledge has stimulated the permanence of new social movements in Goiás and of territorializations in camps and settlements, such as those ones researched here. The interviews done, the speeches analyzed, the memories and the fieldwork with leaderships linked to the rural workers’ unions from 9 municipalities of Goiás (Itapuranga, Bela Vista, Goiânia, Goiás, Faina, Itauçu, Uruaçu, Corumbá de Goiás and Carmo do Rio Verde) have showed changes in the process of training and performance of the leaderships, the alterations in the daily life, and in the world of work. The strengthening of the associations, of joint efforts and practices that integrate the rural communities. The analyzes of the interviews denote that the settlers have knowledge and knowing related to the formal and informal aspects, they still move between religious practices, with less participation in social movements nowadays. The exchange of knowledge among the peasants encourages permanence, in the sense of strengthening the territories. Have observed that the media, the churches, the participation in camps and settlements, the formal school, the fairs, the seminars, the courses of assistance and the training in the unions were the elements capable of influencing the political identity and the actions the field in Goiás.